Influence of Reward Motivation on Directed Forgetting in Younger and Older Adults - Bowen, Holly J.; Gallant, Sara N.; Moon, Diane H. (Frontiers in Psychology, 2020)
An important feature of the memory system is the ability to forget, but aging is associated with declines in the ability to intentionally forget, potentially due to declines in cognitive control. Despite cognitive deficits, older adults are sensitive to affective manipulations, such as reward motivation, and reward anticipation can improve older adults’ memory performance. The goal of the current studies was to examine the effect of reward motivation on directed remembering and forgetting. Participants were healthy CloudResearch/Turk Prime workers aged 18-35 and 60-85. In Experiment 1, we conducted a typical item-method directed forgetting task using neutral words presented one at a time followed by a cue to-be-remembered (TBR) or to-be-forgotten (TBF). A recognition memory test followed that included all words from the encoding task, as well as new words. We replicated prior findings of better memory for items TBR compared to TBF, but not typical age-related differences in recognition of TBF items. In Experiments 2—4, we repeated this paradigm except that in the second block of trials, each word was presented with a high ($.75) or low ($.01) reward cue indicating the value that could be earned if the item was successfully Remembered or Forgotten (depending on cue). During recognition, correct responses to target items (both TBR and TBF) resulted in the associated reward, but incorrect "old" responses resulted in a loss of $.50. In three experiments, high rewards led to better memory for younger and older adults compared to low rewards, regardless of the directed cue to remember or forget the word. In Experiments 3 and 4, older adults showed typical deficits in directed forgetting, but this was across reward conditions. For older adults, there was no evidence that including reward motivation improved cognitive control abilities as high value reward anticipation did not improve directed forgetting. Instead, in line with hypotheses, high compared to low value reward anticipation lead to engagement of processes that resulting in better memory regardless of the TBR or TBF cue, and that reward anticipation bolsters memory in a relatively automatic, rather than strategic, fashion that overrides one’s ability to cognitively control encoding processes.